The impact of electricity market reform in Ukraine on NPC “Ukrenergo” activity - Ущаповський, Костянтин Валерійович; Костін, Юрій Дмитрович (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The impact of electricity market reform inUkraineon NPC “Ukrenergo” activity is analyzed in the article. The effects of reorganization, including segregation of electricity transfer activities from operational dispatch management of integrated power system ofUkraine, are determined. The risks associated with this process are reviewed.